Patisserie Business Development to Support the Quality of Tourist Destinations: Case Study of Greater Bandung - Zeilla Nailurrahmi (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
This study employs a qualitative research approach to investigate the development of patisserie businesses in Greater Bandung and their contributions to enhancing the quality of tourist destinations. By utilizing a descriptive case study design, the research incorporates direct observations of selected patisseries and secondary data from government tourism reports, academic literature, and online reviews. Key focus elements include location accessibility, interior ambiance, product variety, service quality, and tourist engagement. Direct observations provide insights into business operations and customer interactions, while secondary data contextualizes these findings within broader tourism trends. The data analysis employs descriptive and content analysis techniques to identify themes and relationships between patisserie development and tourism growth. Triangulation of data sources enhances the validity and reliability of the findings. Ethical considerations are minimal, as observations occur in public spaces, with transparency maintained regarding the observation process. This methodological framework offers a comprehensive examination of the role of patisserie businesses in Greater Bandung, highlighting their integration into the local tourism landscape and their significant contributions to improving the overall tourist experience. The results underscore the importance of culinary tourism in enhancing the attractiveness of destinations, providing valuable insights for stakeholders aiming to optimize their culinary offerings within sustainable tourism practices.